Etyczny aspekt teorii normatywnych rachunkowości - Rogowska, Beata (Annales. Etyka w Życiu Gospodarczym, 2016)
The aim of this study is to show the ethical aspects of the so-called normative accounting theory (NT), with particular emphasis on the ethical and normative theory (EN) important for the development of accounting as a science, taking into account its social function. Attention is focused on the so-called axiological layer with regard to the methodological foundation (pragmatic methods and related metascience) regarding the work of theorists in Western Europe. Although in the years 70s shall be considered as unscientific and begin the process of domination positive theory of accounting. It seems that in the twentyfirst century takes rebirth specific ethical and social topics in accounting. The importance and usefulness of ethics in accounting due to turbulent environment changes of accounting and social needs, as well as changes within the science.